Part 5a: Solvent chemistry: NMR analysis and studies for amine–CO2–H2O systems with vapor–liquid equilibrium modeling for CO2 capture processes. Issue 2 (April 2012) - Shi, Huancong; Liang, Zhiwu; Sema, Teerawat; Naami, Abdulaziz; Usubharatana, Phairat; Idem, Raphael; Saiwan, Chintana; Tontiwachwuthikul, Paitoon
This is Part 5a of a special review series on recent progress and new developments of the post-combustion carbon-capture technology using reactive solvents. NMR spectroscopy is an important method used in analytical chemistry to test the functional groups and molecular structures of organic compounds. This methodology has been recently applied in CCS in the field of solvent chemistry for aiding the development of novel solvents for capturing CO2 . NMR has been used for testing new amines and amine–CO2 –H2 O systems with 1 H and 13 C spectra for a number of years. This paper is a comprehensive review recent research papers that have applied NMR spectroscopy in the analysis of a variety of amines and a systems for multiple purposes, mostly for vapor–liquid equilibrium model analysis, and for some other qualitative as well as kinetic analyses.